Pengabdian Kepada Masyarakat Mengenai Peran Kuliah Kerja Nyata (KKN) Berbasis Masjid Di Masjid Hidayatullah Desa Kembang Seri - Hesti Nur Aini; Fina Fasmala Sari; Melnia Puspita Sari; Putri Chaira Ummah; Mudahria; Desfi Dwi Yulinda; Lola Delia; Necko Rahmat Novianto; Roges Vin; Rivaldo Agung Wibowo; Yusnelma Eka Afri (jurnal ABDIMAS Indonesia, 2024)
Kuliah Kerja Nyata (KKN) are a means that enable students to apply their theory to real community work. Community service activities can contribute/help improve various community needs and solve various problems faced by the community so that community welfare increases. This research aims to examine the role of KKN to develop mosque activities and support the spread of the Islamic message as well as to implement and practice among the public the importance of environmental awareness. Descriptive and observational methods. KKN students take part in protecting the environment, understanding religion and society for children and adults. Environmental awareness in Kembang Seri Village is increasing continuously. People are starting to maintain cleanliness because cleanliness is part of their faith and children are also showing significant understanding of Islamic religious knowledge through learning carried out by KKN students.